ANALYSIS OF CONSUMER RECEPTIONS TOWARDS LIVE STREAMING TIKTOK SHOP IN ANIMAL AND PLANT SALES ACCOUNTS - Aulia, Rosyada Dinda; Prabayanti, Herma Retno (The Commercium, 2024)
This research aims to analyze consumer reception of live streaming on the TikTok Shop animal and plant account. TikTok social media is one of the most popular platforms for users around the world, including Indonesia, which is ranked second in number of users after America. TikTok Shop is a new innovative feature in Indonesia that provides business opportunities for entrepreneurs to promote their products. However, strict regulations regarding the sale of animals and plants on the TikTok Shop pose challenges for business owners. This research aims to understand how consumers respond and interpret the content presented by sellers in TikTok Shop live streaming. This research uses a qualitative reception analysis approach using the AIDA model and persuasive communication theory. The results of this research are that consumers on TikTok are in a dominant position despite strict regulations, but feel they agree with the policy. As for consumers who are in a negotiating position, consumers feel doubtful due to the regulations on TikTok, but consumers feel confident after interacting with sellers via live streaming sales.